Suku Bunga Bank Indonesia, Financing To Deposit Ratio Dan Kinerja Perbankan Syariah Di Indonesia - Adi Musharianto (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2014)
This research performs to test the influence on Financing to Deposit Ratio (FDR) and interest rate (BI Rate) toward Return on Asset (ROA). The research methodology using quantitative descriptive analysis with purposive sampling, the sample is a number of banks that operates of shari’a system. The result shows that (1) FDR has positive significant influence toward ROA; and (2)BI Ratehas negative significant influence towardROA. Prediction capability from both of these variables toward ROA is 26.50% whereas most of it amounting 73.50% isinfluenced by other factors.